Point-of-Care Ultrasound Training and Credentialing for mid-late Career Emergency Physicians: Is it worth it? - Courtney Smalley; Erin Simon; McKinsey Muir; Fernando Delgado; Baruch Fertel (CINQUILL Medical Publishers Inc., 2021)
Point-of-care ultrasound (POCUS) is becoming more prevalent in community emergency medicine (EM) practice with the current American College of Emergency Physician guidelines recommending POCUS training for all graduates from United States based residency programs as well as support for POCUS privileging by the American Medical Association. However, in a recent survey of nonacademic EDs, it was found that most providers lack US training, credentialing, and quality assurance (QA) assessments of their POCUS studies. In 2017, our healthcare system embarked on a system-wide credentialing process for POCUS to credential community physicians with little to no POCUS training.